Epidemiology of idiopathic pulmonary fibrosis in Europe – an update - Annesi-Maesano, I.; Nunes, H.; Duchemann, et al., B. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Idiopathic pulmonary fibrosis (IPF) is a non-neoplastic pulmonary disease that is characterised by the formation of scar tissue within the lungs in the absence of any known cause. IPF is the most common of the idiopathic interstitial pneumonias and is an important cause of respiratory mortality. IPF is a relatively rare disease with an estimated prevalence ranging from two to 29 cases per 100,000 and slightly higher in men (20.2/100,000) than in women (13.2/100,000). The mean age at presentation is 66 years. Little recent epidemiological data on the prevalence, incidence, risk factors, and mortality related to the disease are available or are limited by methodological weaknesses. Outstanding questions remain, including the causes of IPF, why the incidence is on the rise, and how best to manage this disease. New comparable epidemiological data on IPF are needed.